Potential of native and bioprocessed brewers' spent grains as organic soil amendments - Cacace, Claudio; Cocozza, Claudio; Traversa, Andreina; Coda, Rossana; Rizzello, Carlo Giuseppe; Pontonio, Erica; De Mastro, Francesco; Brunetti, Gennaro; Verni, Michela (Frontiers in Sustainable Food Systems, 2022)
Introduction The use of novel soil amendments and the exploitation of plant growth-promoting microorganisms are considered promising tools for developing a more sustainable agriculture in times when ensuring high-yield productions with limited resources is essential. Methods In this study, the potential of brewers' spent grain (BSG), the major by-product of the brewing industry, as organic soil amendment, was investigated. Bioprocessed BSG, obtained by an enzymatic treatment coupled with fermentation, together with native BSG, were used as amendments in a pot-trial. An integrated analytical approach aimed at assessing the modification of the physicochemical properties of a typical Mediterranean alkaline agricultural soil, and the plant growth-promoting effect on escarole (Cichorium endivia var. Cuartana), was carried out. Results The use of biomasses led to soil organic content and total nitrogen content up to 72 and 42% higher, compared to the unamended soils. Moreover, the lower pH and the higher organic acids content doubled phosphorus availability. Although the number of leaves per plant in escaroles from pots amended with native and bioprocessed BSG did not show any difference compared to plants cultivated on unamended pots, the average fresh weight per escarole head, was higher in pots amended with bioprocessed BSG. Discussion Hence, the results collected so far encourage BSG application for agricultural purpose, while solving the problem of disposing of such abundant side stream.